UPAYA UNIT PATROLI SATUAN SABHARA DALAM PENCEGAHAN TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRES MAJALENGKA - Andry Fauzan Haryano (Police Studies Review, 2017)
The background of this research comes from of the high level of vehicle crime in the region of Polres Majalengka. Despite the prevention attempts that has been done by Unit Patroli Satuan Sabhara Polres Majalengka by mapping regions that are prone of vehicle crime or vehicle theft and dividing patrol routes specific to resolve the crime of vehicle theft. But those attempts haven’t eliminate the crime of vehicle theft from being top three rank from the data of crime total in Polres Majalengka. This research is done to know the description of crime in the region of Polres Majaelngka, the attempt that’s been done by Unit Patroli Satuan Sabhara Polres Majalengka in order to prevent vehicle theft in the region of Polres Majalengka, and factors that affect the attempt of Unit Patroli Satuan Sabhara Polres Majalengka to prevent vehicle theft. This research uses qualitative approach with interview, observation and document studies as the technique of taking data. The result of the research shows that the attempt by Unit Patroli Satuan Sabhara Polres Majalengka is in line with the application of management theory, the prevention attempt is corresponding with the research about description of crime theft in Majalengka. However, there are a few factors that inhibit the prevention attempt when it’s analyzed with theory of performance, which is the limitation of human resources based on quality and quantity, also there’s anomaly of the crime total data that occurred in certain periods. Based on the research, the author suggests enhancement of quality and quantity of human resources of personnel of Unit Patroli Satuan Sabhara by attending courses and education that corresponds with their duty, focus enhancement towards guarding and security in periods that’s pictured in crime total data in order to maximize the prevention attempt of vehicle theft in region of Polres Majalengka. Key word: vehicle crime, vehicle theft, Majalengka, Sabhara, prevention, attempt.